Screening for anorexia nervosa via measurement of serum leptin levels - Föcker, Manuel; Timmesfeld, N.; Scherag, S.; Bühren, K.; Langkamp, M.; Dempfle, A.; Sheridan, E. M.; de Zwaan, M.; Fleischhaker, C.; Herzog, Wolfgang; Egberts, K.; Zipfel, S.; et al. (Journal of neural transmission, 2011)
Due to their sub-normally low fat mass, leptin levels in patients with acute anorexia nervosa (AN) are well below reference levels for age and sex-matched controls. This hypoleptinemia entails endocrinological and behavioral characteristics observed in AN patients during starvation. We aimed to study the appropriateness of hypoleptinemia as a diagnostic marker for AN by assessing sensitivity, specificity and likelihood ratios for different referral serum leptin levels for predicting anorexia nervosa and healthy leanness. For prediction, we additionally generated a score based on a multivariate logistic model including body mass index (BMI; kg/m²) and leptin level. For this purpose, we measured leptin levels in 74 female patients with acute AN upon admission for inpatient or outpatient treatment. Adolescent and adult patients were recruited according to DSM-IV criteria from two multi-center studies. Additionally, leptin levels were measured in 65 female healthy, lean students. Mean serum leptin level was significantly decreased in patients with AN compared to underweight controls (0.87 ± 0.90 vs. 6.43 ± 3.55 μg/L, p < 0.001). Leptin predicted AN independently of BMI; we confirmed a cutoff value in the range of 2 μg/L as having both high specificity and sensitivity. Hypoleptinemia represents a state marker of acute AN and is useful for a laboratory-based diagnostic screening.
Gesehen am 24.01.2023